An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea) - Fallahzadeh, Majid; Japoshvili, George (Zootaxa, 2017)
An updated checklist of Iranian Encyrtidae (Hymenoptera, Chalcidoidea) is presented based on literature records from 1947–2016. The current list includes 159 species representing 48 genera. Parasitoid-host associations in Iran and distributional data are also provided. Twelve encyrtid species (7.55%) are known only from Iran but a high number of species (68 species, 42.77%) are widely distributed in the Palaearctic region. Four species previously listed from Iran, Metaphycus angustifrons Compere, 1957, Homalotylus ephippium (Ruschka, 1923), H. sinensis Xu & He, 1997, and Ooencyrtus kuvanae (Howard, 1910) are no longer considered present. Hosts of Iranian encyrtid species are tabulated by order and family, with the majority being Hemiptera (66.98%), followed by Lepidoptera and Coleoptera (each 9.44%), Diptera (6.60%), Hymenoptera (4.71%) and Neuroptera (2.83%). The majority of Encyrtidae known in Iran are parasitoids of the superfamily Coccoidea (46.22%). Host-plant associations of Iranian Encyrtidae are also tabulated, by plant family.